The RNA polymerase II general transcription machinery - Hampsey, Michael (Henry Stewart Talks, 2007)
Core promoters, Enhancers and silencers, General transcription factors, RNAP II, Mechanism of initiation, Update interview: RNAP II carboxy-terminal domain (CTD), Update interview: mRNA-protein particles (mRNPs), Update interview: Nuclear pores, Update interview: Gene loops, Update interview: Transcription memory, Update interview: Transcription re-initiation
Updated at 2020/10/14